Brand Experience, Brand Image, and Brand Trust to Nike's Loyalty Brand in Jakarta - Margaretha, Rahelia; Rodhiah, Rodhiah (Budapest International Research and Critics University, 2021)
The purpose of this study is to examine and determine the influence of brand experience, brand image, and brand trust on brand loyalty Nike in Jakarta. The research design used in this study is quantitative method with a descriptive approach. Sampling was carried out using a non-probability sampling method with a convenience sampling approach with a total sample 123 respondents who are Nike user in Jakarta. Data collection method is done by distributing online questionnaires. Data analysis techniques used is partial least square-structural equation modeling (PLS-SEM) and using SmartPLS version 3. The results of this study indicate that brand experience, brand image and brand trust can have a positive influence on brand loyalty.